QUALITY OF SCAD MACKEREL (Decapterus sp.) PINDANG PROCESSED AT DIFFERENT LEVELS OF SALTING AND COOKING TREATMENT - Ohoiwutun, Maria Kristina; Tuarita, Mirna Zena; Tumiwa, Bruri Berel; Serpara, Saul Abraham; Nara, Selfia Martha (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2021)
Regarding source of animal protein, pindang (salted and cooked fish) seems to have a greater potentiality than ikan asin (salted and dried fish), since pindang is more favorable in terms of sensory properties; thereby, pindang can be more widely consumed. Besides, pindang is also ready-to-eat product, which make it easier to consume. This research aimed at evaluating the different degree of salting and cooking on quality of scad mackerel pindang. The experiment was carried out according to Randomized Block Design, consisting of two processing methods: steam (A) and pressured or presto (B), with various concentrations of salt, i.e. 5%, 10% and 15%. The sample was then analyzed for content of protein, moisture, ash, as well as hedonic profile. The results showed that the best quality of scad mackerel pindang was achieved at pressured fish with salt 5%, yielding protein of 34,68%, moisture of 64,79%, and ash of 1,80%.